Pengaruh Penggunaan Lb Virtual berbasis PhET Simulation terhadap Kemampuan Berpikir Analitis Siswa - Elmi Mahzum; Abdul Halim; Nazilatul Usfia; Fitria Herliana (Postgraduate, University of Mataram, 2024)
The use of media in the learning process has a very important role. When there are limitations in media use, especially in accessing real laboratories, it can cause a decrease in students' analytical thinking abilities. This research aims to identify the impact of using PhET simulation on students' analytical thinking abilities. This research is included in the type of quasi-experimental research, a quantitative approach with a pretest-posttest control group design. The research sample was taken using a purposive sampling technique, which resulted in two groups, namely 25 students from class XI-MIA 1 as the experimental group, and 25 students from class XI-MIA 2 as the control group. Data was collected using test techniques, with pretest-posttest value data. Data analysis was carried out using the independent sample t-test, and previously prerequisite tests were carried out in the form of normality and homogeneity tests. The results of hypothesis testing show that the value is 0.04 < 0.05, which means the research hypothesis is acceptable. From this research it can be concluded that the use of PhET Simulation has a significant influence on students' analytical thinking abilities.